Mammal distribution and trends in the threatened Ebo 'intact forest landscape', Cameroon - Robin C. Whytock; Ekwoge E. Abwe; Daniel M. Mfossa; Marcel E. Ketchen; Abwe E. Abwe; Vianny R.V. Nguimdo; Fiona Maisels; Samantha Strindberg; Bethan J. Morgan (Global Ecology and Conservation, 2021)
Intact forest landscapes (IFLs) are globally important for maintaining functional ecosystems. Ebo forest (~1400 km2) in Cameroon is one of the largest remaining IFLs in the Cross-Sanaga-Bioko coastal forest ecoregion and harbours several IUCN Red-Listed threatened mammal species. We evaluated the status, trends, and distribution of mammals ≥ 0.5 kg in the Ebo forest over 12 years using guided recce and camera trap monitoring surveys, as well as local knowledge to inform future land use and conservation planning. Recce monitoring of six taxa (blue duiker Philantomba monticola, chimpanzee Pan troglodytes, forest elephant Loxodonta cyclotis, putty-nosed monkey Cercopithecus nictitans, medium sized duikers Cephalophus spp., and red river hog Potamochoerus porcus) showed that some are stable or increasing. Indeed, our recent camera trap data confirmed breeding Gorilla gorilla (western gorilla) and elephant. Distribution models for chimpanzees and elephants showed that their populations are concentrated in the centre of the forest, away from human pressure. Some other species, however, including red colobus Piliocolobus preussi, leopard Panthera pardus, African golden cat Caracal aurata, and forest buffalo Syncerus caffer nanus are either close to extirpation or have been extirpated within living memory. We conclude that the Ebo intact forest landscape retains an important mammal community, despite no formal legal protection. Ebo’s future is uncertain, with two commercial logging concessions announced by Cameroon in 2020 and later suspended in response to national and international pressure. It is crucial to maintain Ebo’s integrity to protect the biodiversity and function of this important part of the Cross-Sanaga-Bioko coastal forest ecoregion.